PENGARUH TAX AVOIDANCE DAN KEPEMILIKAN INSTITUISIONAL TERHADAP COST OF DEBT PADA PERUSAHAAN SEKTOR PERBANKAN - Hidayat, Rheznandya Norman; Darniaty, Will Andilla (Ibs Press, 2025)
This study aims to analyze the influence of Tax Avoidance and Institutional Ownership on the Cost Of Debt in Indonesian banking companies. This study is based on Agency Theory and Trade Off Theory, with the dependent variable being Cost of Debt, while the independent variables are Tax Avoidance and Institutional Ownership. The data used is secondary data obtained from the financial reports of banking companies listed on the Indonesia Stock Exchange (IDX) during a certain period. The research method used is panel data regression to test the relationship between variables. The results indicate that Tax Avoidance and Institutional Ownership significantly influence the Cost of Debt of banking companies. These findings have important implications for management and regulators in managing capital structure and taxation policies in the banking sector.